Investigation of Reservoir Flow Unit and Rock Types of Mishrif Formation in Amara Oil Field and Prediction of Performance - Al-Baldawi, Buraq; Nasser, Madhat (Iraqi Journal of Science, 2023)
Amara oil field is located at south eastern Iraq in Missan governorate. The Mishrif Formation in Amara field is one of the most important reservoirs in southern Iraq. Identifying and characterizing petrophysical flow units are the key to understanding and improving reservoir description, exploitation, production and predicting the performance of carbonate reservoirs to represent them as combinations of different flow units, each with uniform pore throat size distribution and similar performance. Mishrif Formation in Amara oil field was divided into seven reservoir units (MA.MB11,MB12,MB13,MB21,MC1, and MC2) separated between them barrier beds. The present work is a reservoir flow unit identification for (MA) and (MB11) reservoir units of the Mishrif Formation in two wells ,Amara oil Field (Am-1, and Am-3) using available core data. Also Winland's approach was used to predict pore throat types that corresponds to the R35 value which is a function of entry size and pore throat sorting, and is a good measure of the largest connected pore throats in a rock with intergranular porosity. Determined R35 using Winland's model shows the reservoir rock type of MA unit is better than reservoir rock type in MB11 unit. According to R35 values, the pore throat types of Mishrif Formation in MA unit are mostly of meso, micro, macro, and mega type respectively and negligible existences of nano type, where as MB11 unit consists mostly of meso, macro and micro type respectively with few existences of nano pore type and without any mega type. Application of petrophysical flow unit types approach from routine core analysis indicates that MA unit of Mishrif Formation consists of five hydraulic flow units in wells under study where as MB11 unit has four hydraulic flow units.